The Dynamics of the Wood Lathe Industry UD. Indo Trading in Sentul Village, Kepanjenkidul District, Blitar City, 2011-2018 - Umar Farouk Rulianto; kayan swastika; marjono marjono; ahmad ryan pratama (History Education, University of Jember, 2019)
This article discusses the dynamics of the UD lathe industry. Indo Trading 2011-2018. The problem that will be revealed is the factor behind the establishment of the UD lathe industry. Indo Trading in 2011, dynamics which included the development, change and sustainability of UD. Indo Trading. The scope of the material is the industrial elements which include capital, raw materials, labor, production and marketing processes. Factors that influence the establishment of UD. Indo trade can be classified into two types, the first is a factor that directly influences the establishment of UD. Indo Trading, this factor stems from the family's push to continue the family industry that has existed since the range of 1953. The second factor is a factor that affects indirectly, namely geographical factors where this factor is related to the fulfillment of raw materials in the wood lathe industry. In 2016 this industry changed to CV. Sicash Makmor with various changes and complex developments in it including capital, raw materials, labor, production processes and marketing.